Conidial germination and infection level of Exserohilum turcicum (Turcicum leaf blight of maize) at various incubation periods and plant age - S.M. KHANORKAR, S.K. SINGH*, P.K. PARMAR, K.H. PATEL and (Indian Phytopathology, 2016)
The fungal spore germination and infection depends upon incubation period, atmospheric temperature and relative humidity. The spore germination at various incubation periods was found to differ significantly. Maximum germination (92.91%) was observed after 36 hours of incubation, but germination was only 6.38 per cent after four hours of incubation. More than 50 per cent germination was observed after 16 hours of incubation. There was no significant increase in spore germination from 28 to 36 hours of incubation. An incubation period of 28 hours is necessary to achieve more than 90 per cent spore germination. The data revealed that age of the plant has got significant effect on the extent of susceptibility. Plants of all age group, seedling to maturity were found to be infected by E. turcicum, but severity differed significantly with the age of the plant. The disease development started on 25 days (43.27%) and increased progressively upto 75 days (90.34%) and later on became stable. Maximum blight intensity of 95.57 per cent was observed on 55 days old plants which were at par with 65 days (95.04%) and were significantly superior to rest of the plant age group. The present study concluded that plant of age group 55 to 65 days old were highly susceptible to E. turcicum which coincide with silking stage and maximum germination 92.91% was observed after 36 hours of incubation period.